Talent Management as a Strategy for Civil Service Human Resource Development: Analysis of Civil Service Career Development in Banjarbaru City - Annisa Zahra; Budi Kristanto (Dinasti International Journal of Education Management and Social Science, 2025)
Talent management is a strategic instrument in the development of civil service human resources, particularly in realizing a planned, transparent, and merit-based career development system for civil servants (PNS). This study aims to analyze the implementation of talent management as a strategy for civil service human resource development, focusing on career development for PNS in Banjarbaru City. The research method applied is descriptive qualitative with a case study approach at the Personnel and Human Resource Development Agency (BKPSDM) of Banjarbaru City. The Banjarbaru City Government already has a clear legal foundation through Mayor Regulation Number 49 of 2023 concerning the Implementation of PNS Talent Management, which refines Mayor Regulation Number 56 of 2022 and is a follow-up to Ministerial Regulation of Administrative and Bureaucratic Reform (PermenPAN-RB) Number 3 of 2020. Since the regulation was enacted, the City Government has conducted talent management assessment centers for 2,282 civil servants during the 2023–2025 period, which were then mapped into 9 talent boxes. Out of a total of 2,282 civil servants who were mapped, the results have not yet been fully followed up through promotions, rotations, or succession planning, indicating that the implementation is still at an early stage. Theoretically, this study emphasizes the role of talent management in PNS career development as a sustainable strategy for civil service human resource development. Practically, this study recommends strengthening the merit system, expanding access to competency development, and digitizing the talent management process to support transparency and effectiveness in PNS career development in Banjarbaru City.